2022
DOI: 10.1099/mic.0.001244
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 biosynthesis of Cetobacterium ceti isolated from the intestinal content of captive common bottlenose dolphins (Tursiops truncatus)

Abstract: In comparison with terrestrial mammals, dolphins require a large amount of haemoglobin in blood and myoglobin in muscle to prolong their diving time underwater and increase the depth they can dive. The genus Cetobacterium is a common gastrointestinal bacterium in dolphins and includes two species: C. somerae and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The main metabolite of Cetobacterium is acetic acid, which can regulate the expression of insulin and promote the utilization of sugar by the body (Wang et al, 2021). Cetobacterium can also improve the body's metabolism of amino acids and promote the body's utilization of protein (Suzuki et al, 2022;Zhang et al, 2022). The results of this experiment show that ELM can improve the digestion and utilization of sugar and protein in the intestinal tract of spotted sea bass by increasing the activity of intestinal amylase and trypsin.…”
Section: B a Figurementioning
confidence: 82%
“…The main metabolite of Cetobacterium is acetic acid, which can regulate the expression of insulin and promote the utilization of sugar by the body (Wang et al, 2021). Cetobacterium can also improve the body's metabolism of amino acids and promote the body's utilization of protein (Suzuki et al, 2022;Zhang et al, 2022). The results of this experiment show that ELM can improve the digestion and utilization of sugar and protein in the intestinal tract of spotted sea bass by increasing the activity of intestinal amylase and trypsin.…”
Section: B a Figurementioning
confidence: 82%
“…Functional studies revealed that Cetobacterium spp. synthesize vitamin B 12 , which has been shown to improve host resistance against pathogen infection [ 92 , 93 ]. The exact role of these Fusobacteriota in the microbiome of Coelopa frigida remains elusive, but its abundance in larval samples suggests a possible important role.…”
Section: Discussionmentioning
confidence: 99%
“…Cetobacterium (ASV015), a member of Fusobacteriaceae like the highly abundant Fusobacterium , is not common within the gut microbiota of terrestrial animals but has been found in other native Australian mammals such as Tasmanian devils (Cheng et al, 2015) and platypus (Dungan & Thomas, 2023). This genus can assist in carbohydrate and peptide fermentation and is suggested to produce vitamin B 12 , which is essential for the biosynthesis of heme, a component of hemoglobin and myoglobin, that cannot be produced by mammals (Bhute et al, 2020; Suzuki et al, 2022). Streptococcus (ASV022), on the other hand, is associated with disease in echidnas (McOrist & Smales, 1986).…”
Section: Discussionmentioning
confidence: 99%